Розвиток координаційних здібностей спортсменів-волейболістів на етапі спеціалізованої базової підготовки - Павлов, Дмитро Андрійович; Pavlov, Dmytro Andriyovych (Ірпінь, 2024)
Рівень розвитку сучасного волейболу в Україні, участь українських волейболістів у міжнародних змаганнях та зростання конкуренції вимагають безперервного вдосконалення навчально-тренувального процесу і виявлення дійових засобів підвищення підготовки волейболістів. Широкий спектр факторів, від яких залежить успішність ігрової діяльності, зумовлює важливість розвитку та вдосконалення координаційних здібностей волейболіста, відповідно до вимог ігрової обстановки. Розвиток та вдосконалення координаційних здібностей в сукупності з фізичними властивостями сприяє вирішенню важливих завдань по вдосконаленню фізіологічних систем організму. Координаційними здібностями, які в тій або іншій мірі відображають характер рухової діяльності людини, є: спритність, гнучкість, ритмічність, рівновага, стрибучість, влучність, точність, рухливість, пластичність. В кваліфікаційній роботі обгрунтовується запропонована програма підвищення координаційних здібностей волейболістів і доводиться її ефективність.

The level of development of modern volleyball in Ukraine, the participation of Ukrainian volleyball players in international competitions and the growth of competition require continuous improvement of the educational and training process and the identification of effective means of improving the training of volleyball players. A wide range of factors on which the success of the game depends, determines the importance of the development and improvement of the volleyball player's coordination abilities, in accordance with the requirements of the game environment. The development and improvement of coordination abilities in combination with physical properties contributes to the solution of important tasks to improve the physiological systems of the body. Coordination abilities, which to one degree or another reflect the character of a person's motor activity, are: dexterity, flexibility, rhythmicity, balance, jumping, accuracy, accuracy, mobility, plasticity. The qualification work substantiates the proposed program for improving the coordination abilities of volleyball players and proves its effectiveness.
Development of coordination abilities of volleyball athletes at the stage of specialized basic training
Keywords: координаційні здібності; навчально-тренувальний процес; волейболісти; методика розвитку; coordination abilities; educational and training process; volleyball players; development method